Vestibular and cochlear dysfunction in aging: Two sides of the same coin?. Issue 4 (18th April 2022) - Azevedo, Cátia; Vilarinho, Sérgio; Sousa Menezes, Ana; Milhazes Mar, Fernando; Dias, Luís
Abstract: Objective: Nonspecific complaints of hearing loss, vertigo, imbalance, and instability, without a defined etiology, are very prevalent in the elderly population, with a great impact on morbidity and mortality in this age group. The objectives of this study were to verify whether there is age‐related vestibular dysfunction and to test the association of vestibular dysfunction with presbycusis in the elderly population. Methods: Original retrospective analytical cross‐sectional study, carried out with 80 patients who underwent a videonystagmography and complete audiometric evaluation due to nonspecific vestibular complaints, without a specific vestibular disorder diagnosis. Patients were selected and divided into two distinct age groups (group A: >60 years; group B: 18–50 years) and, in both groups, we analyzed the caloric tests and the pure‐tone audiometry. Results: In the vestibular evaluation, we found that there was a statistically significant difference ( P  < 0.05) between groups in the prevalence of bilateral vestibular weakness (group A: 22.5%; group B: 5%), and that the increase in age, above 60 years, is negatively correlated with the mean total caloric response. Additionally, we obtained a reasonable negative and statistically significant correlation ( r  = −0.320, P  < 0.05) between the mean bone conduction thresholds at high frequencies and total caloric responses in group A. Conclusions: In patients with hearing loss, it is essential to perform a complete vestibular study to diagnose vestibular disorders and, consequently, prevent adverse outcomes that may result from these alterations.